Determination of NaCl- induced modifications in growth processes and induction of programmed cell death in sunflower roots - Mackievic, Viera S.; Zvanarou, Siarhej M.; Shyker, Artur A.; Turovets, Oksana A.; Smolich, Ihar I.; Sokolik, Anatoly I.; Demidchik, Vadim V. (Experimental Biology and Biotechnology, 2019)
Globally, about 30 % of all soils are damaged by salinity. Salinity leads to lower productivity of agro- and biocenosis, a decline in biodiversity and, as a result, significant economic losses. For the most important oil culture – sunflower (Helianthus annuus L.), primary reactions to salt stress are almost unexplored. This paper analyzes the impact of a wide range of NaCl concentrations on the growth of the main root of sunflower sprouts and the development of programmed cell death processes in trichoblasts. Experiments have shown that sunflower plants are relatively resistant to salinity (NaCl). They were able to grow at the level up to NaCl 250 mmol/L in the environment. Significant symptoms of programmed cell death were detected only at high concentrations of NaCl 250 –500 mmol/L. Previously undescribed in the literature, the reaction of reducing the number of symptoms of programmed cell death under150 mmol/L NaCl treatment (medium salt stress level for sunflower) was determined. An inhibitory analysis of the NaCl-induced potassium flux showed that it was only 15 % inhibited by specific potassium channel antagonists (Ba2+ ). This indicates a low proportion of potassium channels and the dominant role of non-selective cation channels in providing NaCl-induced potassium loss in Helianthus annuus L. plants.